The Role of Digital Technology in Social Interaction of Manembo-Nembo Village Community, Matuari District, Bitung City - Kawung, Evelin; Tulung, Lingkan E. (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The purpose of this study is to determine the role of digital technology in social interaction in the Manembo-Nembo Village, Matuari District, Bitung City using the technological determinism theory approach, believing that technology has a major influence on various aspects of human interaction, especially social and cultural life, as stated by Marshall McLuhan. Using qualitative methods based on observation and interviews by collecting data from purposive sampling, namely determining competent informants, namely 2 community informants, 2 government informants. The results of the study found that the role of digital technology in social interaction has changed according to current circumstances, such as digitalization, such as in families it is easier and faster to interact via digital media with relatives who are in different places, the quality of relationships is maintained by having direct meetings in family groups (arisan), then digital interaction with the community; the creation of virtual togetherness such as people celebrating happy moments virtually by sharing photos, videos, and stories, and sharing information about sad events experienced and becoming a means of digital marketing that can increase family economic income. Digital interaction with the government; in today's public services digitally, especially in the field of population data management (KTP, Family Card, Certificate management) has been done through applications and can be done anywhere, but if there are people who need help, the local government is ready to serve, in accordance with the policy of the Bitung city government to make the Kelurahan Hebat program (digitalization).